2019
DOI: 10.1038/s41551-019-0357-8
|View full text |Cite
|
Sign up to set email alerts
|

Adenine base editing in an adult mouse model of tyrosinaemia

Abstract: Unlike traditional CRISPR-Cas9 homology-directed repair, base editing can correct point mutations without supplying a DNA-repair template. Here, we show in a mouse model of tyrosinemia that hydrodynamic tail-vein injection of plasmid DNA encoding the adenine base editor (ABE) and a single guide RNA can correct an A>G splice-site mutation. ABE treatment partially restored splicing, generated fumarylacetoacetate hydrolase (Fah)-positive hepatocytes in the liver, and rescued weight loss in the animals. We also ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 33 publications
7
136
0
Order By: Relevance
“…The A‐to‐G editing efficiency of PCSK9 in the liver by dual‐AAV split‐ABE‐Rma573 is ≈6% (Figure 4d,e), which might meet the requirement for treating recessive genetic diseases. [ 18a,23 ] Significant reductions of PCSK9 protein level (≈50% reduction, 100 mg mL −1 in control mice, 50 mg mL −1 in split‐ABE‐Rma573 targeted mice) and lower VLDL/LDL (very low‐density lipoproteins/low‐density lipoproteins) level (≈0.2–≈0.15 ng mL −1 ) were observed through AI‐MAST strategy (Figure 4f,g), without long‐term liver damage in 6–8 weeks post‐injection (Figure 4h). Our data further highlighted that the intein based dual‐AAV split‐ABE system could induce A‐to‐G editing in vivo, representing an important tool for investigating gene function in adult animal and gene therapy in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…The A‐to‐G editing efficiency of PCSK9 in the liver by dual‐AAV split‐ABE‐Rma573 is ≈6% (Figure 4d,e), which might meet the requirement for treating recessive genetic diseases. [ 18a,23 ] Significant reductions of PCSK9 protein level (≈50% reduction, 100 mg mL −1 in control mice, 50 mg mL −1 in split‐ABE‐Rma573 targeted mice) and lower VLDL/LDL (very low‐density lipoproteins/low‐density lipoproteins) level (≈0.2–≈0.15 ng mL −1 ) were observed through AI‐MAST strategy (Figure 4f,g), without long‐term liver damage in 6–8 weeks post‐injection (Figure 4h). Our data further highlighted that the intein based dual‐AAV split‐ABE system could induce A‐to‐G editing in vivo, representing an important tool for investigating gene function in adult animal and gene therapy in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…To date, seventh generation ABEs (ABE7) have enabled efficient A•T to G•C conversion in the genomes of humans 5 , mice [6][7][8] , bacteria 1 , plants 9,10 , and a variety of other species, reviewed here 11 . Many therapeutic targets, however, may benefit from a more active ABE with a broader editing window or improved compatibility with non-NGG nCas9s [12][13][14] as well as increased editing efficiencies in human cell lines 15 or when used in vivo 8 .…”
mentioning
confidence: 99%
“…injection method induced specific genomic correction of the Fah splicing mutation (Yin et al 2014;Song et al 2019;Yin et al 2016). Another group reported that the application of a combination of viral and lipid nanoparticle-mediated systems of delivery of the SpCas9 mRNA, gRNA, and repair template DNA enables specific correction of the Fah splicing mutation in a Fah5981SB mouse model .…”
Section: Mice and Ratsmentioning
confidence: 99%